2021
DOI: 10.7150/jca.51023
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA RP11-379k17.4 derived microRNA-200c-3p modulates human endometrial cancer by targeting Noxa

Abstract: Objective: The research paid close attention to the function of lncRNA-related endogenous competitive RNAs (ceRNAs) network in endometrial cancer (EC). Methods: 45 primary endometrial cancer tissues (EC) and 45 normal endometrium (NE) were included in the research. The online software StarbaseV2.0 was made use of forecasting the lncRNA which most likely contained microRNA-200c-3p combining sites and could interact with microRNA-200c-3p. Subsequently, we chose lncRNAs which were consistent with the characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…A previous study by the authors demonstrated that miR-205-5p targets the lncRNA LA16c-313D11.11, with one conserved target site in EC. LA16c-313D11.11 may inhibit the expression and activity of miR-205-5p in normal and cancer tissues via this post-transcriptional binding (18). In the present study, LA16c-313D11.11 was shown to modulate a miR-205-5p-PTEN axis in EC.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…A previous study by the authors demonstrated that miR-205-5p targets the lncRNA LA16c-313D11.11, with one conserved target site in EC. LA16c-313D11.11 may inhibit the expression and activity of miR-205-5p in normal and cancer tissues via this post-transcriptional binding (18). In the present study, LA16c-313D11.11 was shown to modulate a miR-205-5p-PTEN axis in EC.…”
Section: Introductionsupporting
confidence: 53%
“…A previous study by the authors demonstrated that LA16c-313D11.11 was associated with the nosogenesis of EC and was shown to be a non-coding RNA. LA16c-313D11.11 is an effective ceRNA which is associated with a miRNA-205-5p-PTEN network (18). To further elucidate the molecular mechanisms through which LA16c-313D11.11 may be involved in endometrial cancer, in the present study, 60 primary endometrial cancer tissues, 20 EAH tissues and 20 normal endometrium tissues were obtained for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous studies have proposed that lncRNAs function a critical role in modulating gene expression at both transcriptional and posttranscriptional levels [ 31 ]. Increasing evidence supported that lncRNAs were implicated in various cancers involving EC development [ 32 ]. For example, lnc-PICSAR affected REV3L expression and improved DDP resistance in cutaneous squamous cell carcinoma [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…At first, we investigated the detailed function of RP11-395G23.3 in ATC. lncRNA RP11-395G23.3, with the length of 1318 bp, is mapped to the site of 106270144-106272899 of chromosome 8, and is rarely studied, only one research indicates that RP11-395G23.3 plays a crucial role in endometrial carcinogenesis by acting as an endogenous sponge RNA to capture miR-205-5p (Xin et al, 2015), however, the relative research on other cancers is lacking. Here we showed that RP11-395G23.3 level was significantly upregulated in ATC cells compared to control cells, which suggested that RP11-395G23.3 expression is involved in the progression of ATC.…”
Section: Discussionmentioning
confidence: 99%